Return to the Forgotten Ultraluminous X-Ray Source: A Broadband NICER+NuSTAR Study of NGC 4190 ULX-1 - Hannah P. Earnshaw; Matteo Bachetti; Murray Brightman; Felix Fürst; Fiona A. Harrison; Matthew Middleton; Renee Ludlam; Sean N. Pike; Daniel Stern; Dominic J. Walton (The Astrophysical Journal, 2024)
We observed the nearby and relatively understudied ultraluminous X-ray source (ULX) NGC 4190 ULX-1 jointly with Neutron Star Interior Composition Explorer (NICER) and NuSTAR to investigate its broadband spectrum, timing properties, and spectral variation over time. We found NGC 4190 ULX-1 to have a hard spectrum characterized by two thermal components (with temperatures ∼0.25 and ∼1.6 keV) and a high-energy excess typical of the ULX population although the spectrum turns over at an unusually low energy. While no pulsations were detected (with pulsed fraction 3 σ upper limits of 16% for NICER and 35% for NuSTAR), the source shows significant stochastic variability, and the covariance spectrum indicates the presence of a high-energy cutoff power-law component, potentially indicative of an accretion column. Additionally, when fitting archival XMM-Newton data with a similar model, we find that the luminosity–temperature evolution of the hot thermal component follows the behavior of a super-Eddington slim disk though the expected spectral broadening for such a disk is not seen, suggesting that the inner accretion disk may be truncated by a magnetic field. Therefore, despite the lack of detected pulsations, there is tantalizing evidence for NGC 4190 ULX-1 being a candidate neutron star accretor although further broadband observations will be required to confirm this behavior.